Building a Better Droplet Generator: Examination of Brown University Harris Laboratory's Schematics and Design - Clark, Nicolette (URJ-UCCS: Undergraduate Research Journal at UCCS, 2020)
We here present the results of a semester project to assemble a piezoelectric droplet generator to produce millimetric oil drops for use in experimental research of a macroscopic system analogous to Louis de Broglie’s pilot wave theory of quantum mechanics. The 3D-printed droplet generator is an inexpensive alternative to commercially-produced equipment and may be fabricated from readily available components. This droplet generator was constructed according to a design by Dr. Daniel Harris of the Massachusetts Institute of Technology’s Harris Lab. We discuss the function and assembly of the droplet generator and recommend a modification to improve performance and ease of use.